Soil utilization of solid waste: Small-strain dynamic properties and microscopic mechanism of phosphogypsum-modified coastal cement soil - Yingdi Pang; Na Li; Meixin Fan; Ping Jiang; Aizhao Zhou; Wei Wang (Journal of Materials Research and Technology)
Phosphogypsum (PG), a solid waste from the wet process phosphoric acid industry, but the utilization rate is low at present. The effect of phosphogypsum and cement on small strain dynamic characteristics of coastal soft soil was studied by resonance column test, and characterize the micro-mechanisms of the specimens by SEM and EDS test. The results show that the dynamic shear modulu (G) and the damping ratio (D) firstly increase and then decrease with the PG level increasing. PG can motivate the formation of hydrated calcium silicate (C–S–H) gel and react with calcium aluminate to form calcium. The critical value for assessing the dynamic behavior of PCS under small strain is γ = 10−4. The Hardin-Drnevich model eigenmodel can well characterize the dynamics of the PCS. Based on this model, a modified dynamic model is established to describe the dynamic characteristics of PCS. The microscopic results showed that the addition of phosphogypsum promoted the production of hydration products and made the particles more closely arranged. The content of this study provides a new reference for the application of solid waste phosphogypsum in cement soil.